Effect of sewage sludge application on heavy metals contamination in soil and carrot. Issue 1 (November 2020) - Schiptsova, N; Larionov, G; Vasilyev, O; Fadeeva, N; Terentyeva, M
Abstract: One of the many environmental problems in the modern world is the disposal of production and consumption waste, including sewage sludge. The aim of our research was to study the content and accumulation of heavy metals in soil and carrots when using increasing doses of sewage sludge as fertilizer and its effect on the yield of products. Sewage sludge with a moisture content of 44.5% was introduced into gray forest soils. After fertilizing the soil, agrochemical analyzes of soil samples from the plots of the experimental plot for the content of heavy metals were carried out. We also studied the content of heavy metals in carrot biomass and its yield. It was found that the content of heavy metals in various variants of experiments with the use of sewage sludge increased. It was found that the dynamics of migration of heavy metals into the biomass of carrots correlates with an increase in their concentration in the soil and affects the yield of carrots.